An adaptive genetic algorithm-based and AND/OR graph approach for the disassembly line balancing problem. Issue 9 (2nd September 2022) - Chen, James C.; Chen, Yin-Yann; Chen, Tzu-Li; Yang, Yu-Chia
Abstract : Manufacturers need to arrange the recovery of product components and subassemblies for reuse, remanufacture and recycling to extend the life of materials in use and reduce the disposal volume owing to increasing environmental concerns. The disassembly line balancing problem (DLBP) is the process of allocating a set of disassembly tasks to an ordered sequence of workstations. A novel mathematical model is presented for the DLBP by considering resource and labour constraints. Utilizing a transformed AND/OR graph as the main input ensures the feasibility of the precedence relationships among the tasks. The objective is to minimize the number of labourers used under the predetermined cycle time. This study proposes a three-phase heuristic adaptive genetic algorithm (AGA) to optimize the number of labourers in the disassembly line. Experimental results indicate that the proposed method is superior to the existing approaches for medium- and large-scale DLBPs.